Influence of Alcohol Advertising on Alcohol Consumption among School Students (Voice: A Biannual & Bilingual Journal, 2023)
Alcohol advertising refers to the advertising of alcoholic beverages by alcohol manufacturers through various media. Exposure to alcohol advertising is the most important leading factor related to alcohol consumption among adolescents and youth. This study is focused on influences of alcohol advertising on alcohol consumption among school students. This study was based on online cross-sectional survey design. All of the secondary school students studying at the schools of Banke district were the population of the study. The researcher included the total 156 secondary school students as a study population by using a multistage sampling method. The data were collected from July 12, 2021 to July 29, 2021 through Google from. The collected data were analyzed by using SPSS version 20, including frequency, percentage, median, mode and chi-square test. This study found that 88.6 percent of the respondents had seen alcohol advertising. Likewise, 31.4 percent of the respondents agreed and 32.7 percent of the respondents disagreed that they pay attention to alcohol advertising on social media. Similarly 85.9 percent of the respondents reported that alcohol advertising increases the number of drunks. Furthermore one fifth of the respondents indicated that alcohol advertising attracts them to taste alcohol. Lastly, this research revealed that there is a weak positive association between respondents who see alcohol advertising and attract them to taste alcohol. It is learned that alcohol advertising influences the purchasing and drinking behaviour of school students. School age is not a legal age for purchasing and drinking alcohol so it is necessary to conduct awareness programs through formal and informal institutions.